2019
DOI: 10.1002/psp4.12462
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis for Imipenem–Relebactam in Healthy Volunteers and Patients With Bacterial Infections

Abstract: Relebactam is a small-molecule β-lactamase inhibitor developed as a fixed-dose combination with imipenem/cilastatin. The pharmacokinetics of relebactam and imipenem across 10 clinical studies were analyzed using data from adult healthy volunteers and patients with bacterial infections. Renal function estimated by creatinine clearance significantly affected the clearance of both compounds, whereas weight and health status were of less clinical significance. Simulations were used to calculate probability of join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 19 publications
3
54
0
Order By: Relevance
“…When evaluating the pharmacokinetics of IMI‐REL IMI 500 mg–REL 250 mg every 6 hours in available patient data, the authors suggested that the f AUC/MIC 0–24 hr of 7.5 would have been achieved in all patients with bacterial isolates with MIC values ≤ 4 µg/ml. In the pharmacokinetic model performed by researchers, the probability of attaining this target was > 90% for isolates with IMI‐REL MIC values ≤ 4 µg/ml, including patients with dose reductions based on their renal function …”
Section: Pharmacodynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…When evaluating the pharmacokinetics of IMI‐REL IMI 500 mg–REL 250 mg every 6 hours in available patient data, the authors suggested that the f AUC/MIC 0–24 hr of 7.5 would have been achieved in all patients with bacterial isolates with MIC values ≤ 4 µg/ml. In the pharmacokinetic model performed by researchers, the probability of attaining this target was > 90% for isolates with IMI‐REL MIC values ≤ 4 µg/ml, including patients with dose reductions based on their renal function …”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…76 Recently, researchers pooled pharmacokinetic data from 10 IMI-REL studies, including patients with cIAI, cUTI, and hospital-acquired or ventilator-associated bacterial pneumonia (HABP/ VABP). 77 These patients also had varying levels of renal function, including some who underwent hemodialysis, allowing for estimation of pharmacokinetics in these important patient populations. The authors evaluated the effects of several covariates, and renal function had the most important impact on IMI-REL concentrations.…”
Section: Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The exposures from this increased regimen were confirmed to be adequate upon completion of this study [ 71 ]. A population pharmacokinetic analysis that took ARC into consideration was performed for imipenem/relebactam [ 72 ]. It found a more than 90% probability of target attainment (PTA) when using a 500/250 mg dose against an imipenem MIC of 4 mg/L when creatinine clearance is 90 to 250 mL/min.…”
Section: Effects On Antibiotic Therapymentioning
confidence: 99%
“…Relebactam-imipenem is currently being evaluated for the treatment of Gram-negative bacterial infections, including hospital-acquired bacterial pneumonia, ventilator-associated bacterial pneumonia, complex intraperitoneal infection, and urinary tract infection caused by MDR pathogens, especially P. aeruginosa and carbapenemase-producing E. coli , K. pneumoniae , and Enterobacter [ 74 76 ]. Prescription of imipenem combined with relebactam for the treatment of Gram-negative bacterial infections is currently in phase III of a clinical trial [ 41 ].…”
Section: Antibiotic-antibiotic Conjugates (Aacs)mentioning
confidence: 99%